ADJUSTMENT OF PROBABILITY FUNCTIONS TO WATER EXCESS AND DEFICIT IN SOYBEANS CULTIVATED IN LOWLAND SOILS - Bortoluzzi, Mateus Possebon; Heldwein, Arno Bernardo; Trentin, Roberto; Nied, Astor Henrique; Silva, Jocélia Rosa da; Rocha, Leidiana da (IRRIGA, 2020)
ADJUSTMENT OF PROBABILITY FUNCTIONS TO WATER EXCESS AND DEFICIT IN SOYBEANS CULTIVATED IN LOWLAND SOILS MATEUS POSSEBON BORTOLUZZI¹; ARNO BERNARDO HELDWEIN²; ROBERTO TRENTIN³; ASTOR HENRIQUE NIED²; JOCÉLIA ROSA DA SILVA4 E LEIDIANA DA ROCHA4 1 Faculdade de Agronomia e Medicina Veterinária, Universidade de Passo Fundo, BR 285, São José, 99052-900, Passo Fundo, RS, Brasil. mateusbortoluzzi@upf.br 2 Departamento de Fitotecnia, Universidade Federal de Santa Maria, Avenida Roraima, n° 1000, Camobi, 97010-900, Santa Maria, RS, Brasil. heldweinab@smail.ufsm.br; astor.nied@ufsm.br 3Departmento de Fitotecnia, UFPel, Campus Universitário, s/n, 96010-610, Capão do Leão, RS, Brasil. roberto.trentin@ufpel.edu.br 4 Programa de Pós-graduação em Agronomia, Universidade Federal de Santa Maria, Avenida Roraima, n° 1000, Camobi, 97010-900, Santa Maria, RS, Brasil. joceliarosa.s@gmail.com; leidi-r1@hotmail.com 1 ABSTRACT The objective of this study was to verify the fit of exponential, gamma, lognormal, normal and weibull probability density functions (pdf) to water deficit and excess accumulated data during soybean subperiods and development cycle. Historical series of meteorological data obtained from Pelotas and Santa Maria meteorological stations (RS) were utilized. The soybean development simulation was performed for cultivars from the relative maturity group (RMG) between 5.9-6.8, 6.9-7.3 and 7.4-8.0 on eleven sowing dates from September 21 to December 31. Daily sequential water balance was calculated with water excess (days) and water deficit (mm) data to adjust each pdf to the observed data. The better adjustment frequency for water excess data in the soybean cycle was obtained with normal pdf in Santa Maria and weibull and gamma in Pelotas. Regardless of the location, the lognormal pdf presented the best fit for the water deficit data in the soybean cycle. In both locations, normal and weibull pdf demonstrated the best performance for water excess in the subperiods gamma, lognormal and exponential pdf for the water deficit. Keywords: Glycine max, risk analysis, sowing date, historical series. BORTOLUZZI, M. P.; HELDWEIN, A. B.; TRENTIN, R.; NIED, A. H.; DA SILVA, J. R.; DA ROCHA, L. AJUSTE DE FUNÇÕES DE PROBABILIDADE AO EXCESSO E DÉFICIT HÍDRICO NA SOJA EM TERRAS BAIXAS 2 RESUMO O objetivo deste trabalho foi verificar o ajuste das funções densidade de probabilidade (fdp) exponencial, gama, lognormal, normal e weibull aos dados de déficit e excesso hídrico, acumulados durante subperíodos e ciclo de desenvolvimento da soja. Foram utilizadas séries históricas de dados meteorológicos obtidos das estações meteorológicas de Pelotas e de Santa Maria, RS. Foi simulado o desenvolvimento da soja, para cultivares de grupo de maturidade relativa (GMR) entre 5.9–6.8, 6.9–7.3 e 7.4–8.0 em onze datas de semeadura compreendidas entre 21 de setembro e 31 de dezembro. Calculou-se o balanço hídrico sequencial diário, sendo obtidos os dados de excesso hídrico (dias) e déficit hídrico (mm) para ajustar cada fdp aos dados observados. A maior frequência de ajuste para os dados de excesso hídrico no ciclo da soja foi obtida para a fdp normal em Santa Maria e fdp weibull e gama para Pelotas. A fdp lognormal foi a que melhor se ajustou aos dados de déficit hídrico no ciclo da soja, independentemente do local. Em ambos os locais, a fdp normal e a weibull apresentaram o melhor desempenho para o excesso hídrico nos subperíodos e as fdps gama, lognormal e exponencial para o déficit hídrico. Palavras-chave: Glycine max, análise de risco, data de semeadura, séries históricas.